Estimating a University Brand in the New Economic Conditions: Concept, Principles, Technique - Pashkus, Vadim Yu.; Pashkus, Natalie A.; Krasnikova, Tatiana S.; Asadulaev, Asadula B. (International Journal of Economics and Financial Issues, 2015)
This article presents a technique for estimating a university’s brand in the new economic conditions. Branding gives a possibility to create tangible, intangible and imagined differences among institutions of higher education based on resource approach in strategic management. The forming of image, reputation and brand is based on key factors of success and core competence. Well-developed brand of educational institution is a basis for the loyalty of its customers, sustainable international connections, guaranteed level of enrollment and competition and ensures the influx of additional financial resources. In the new economic conditions image and brand of public sector institutions are closely connected with the development of the human capital of these institutions, therefore a lack of motivation can have a negative impact on the public image. Monitoring of brand strength allows taking early measures on the complex development of the public sector institutions’ resource potential in order to increase its competitiveness on the basis of image and brand. The presented technique uses the integration of known methodologies: The Boston Consulting Group, Kevin Keller and Young & Rubicam. Keywords: public sector, brand, brand evaluation, Keller method, Y&R method, BCG matrix, brand value, brand advantage JEL Classifications: I21; M37